2013
DOI: 10.1002/marc.201200827
|View full text |Cite
|
Sign up to set email alerts
|

Polymerized Ionic Liquid as Stabilizer in Aqueous Emulsion Polymerization Enables a Hydrophilic–Hydrophobic Transition during Film Formation

Abstract: Polymerized ionic liquid (PIL) nanoparticles are for the first time applied as sole stabilizers in aqueous emulsion polymerization and reveal an astonishing and unexpected behavior. In a well-dispersed state, the PIL nanoparticles serve as an unexpectedly effective stabilizer for polystyrene dispersions, enabling solids content of greater than 40%. However, the same PIL as dry powder is hydrophobic and, in accordance with Bancroft's rule, unable to stabilize aqueous dispersions. This ambivalent behavior of PIL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 35 publications
(33 reference statements)
1
13
0
Order By: Relevance
“…They were able to synthesize latex with a solids content of up to 45% and a particle size of 123 nm. This was the first example of an effective stabilization for emulsion polymerizations that turns hydrophobic in the film after processing, opening a new pathway towards an ideal stabilizer system for emulsion polymers . We and others recently demonstrated the emulsion polymerization of ionic liquid monomers and new applications of poly(ionic liquids) as all‐in‐one reactant and stabilizer for the synthesis of polymer latexes and hydrophobic powders which may lead to stable liquid marbles .…”
Section: Introductionmentioning
confidence: 96%
“…They were able to synthesize latex with a solids content of up to 45% and a particle size of 123 nm. This was the first example of an effective stabilization for emulsion polymerizations that turns hydrophobic in the film after processing, opening a new pathway towards an ideal stabilizer system for emulsion polymers . We and others recently demonstrated the emulsion polymerization of ionic liquid monomers and new applications of poly(ionic liquids) as all‐in‐one reactant and stabilizer for the synthesis of polymer latexes and hydrophobic powders which may lead to stable liquid marbles .…”
Section: Introductionmentioning
confidence: 96%
“…Due to their distinctive physicochemical properties of low volatility, thermal and chemical stability, ability to dissolve organic/inorganic solutes and gases, and tunability of cations and anions, ionic liquids have been widely applied in many fields. [23][24][25][26][27][28][29][30] Former research has already demonstrated that ionic liquids had a great ability for dissolving biomass, [31][32][33][34][35][36][37][38][39][40] based on which a new route for the preparation of biomassbased materials was invented. 27,[41][42][43][44][45][46][47][48][49] Some ionic liquids, such as [AMIM]Cl, 50 [EMIM]Ac, 51 [BMIM]Ac, 33,52,53 [BMIM]C, 51,52,[54][55][56][57] [EMIM][Me 2 PO 4 ] 47 and [BMIM]dca 33,52,58 have been used as solvents for the esterification of natural starch, and the acylated starch could be well dissolved in common organic solvents such as DMF, which is a good solvent for carrying out the ATRP reaction.…”
Section: Introductionmentioning
confidence: 99%
“…So far a broad library of PILs with tunable architectures and properties has been developed through combinations of ammonium, pyridinium, imidazolium, 1,2,3‐triazolium or phosphonium cations with anions such as halides (e.g., Br − , I − ), inorganic fluorides (e.g., PF 6 − , BF 4 − ), or perfluorinated sulfonimides [e.g., (CF 3 SO 2 ) 2 N − , (CF 3 CF 2 SO 2 ) 2 N − ] . PILs have shown promising performances in applications including dye‐sensitized solar cells, fuel cells, light‐emitting electrochemical cells, batteries, sensors, actuators, field‐effect transistors, electrochromic devices, switchable surfaces, permselective membranes, (nano)composites, and catalysis . Most synthetic approaches toward development of PILs involve the direct polymerization of IL monomers or the post‐polymerization chemical modification of neutral polymers into charged ones.…”
Section: Introductionmentioning
confidence: 99%